Students’ Perception on the Implementation of Online Project-Based Learning in Teaching 4Cs - Haniah, Amanda Ummu; Ngadiso, Ngadiso; Setyaningsih, Endang (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Project-based Learning is still being a prominent method to be investigated. As the rapid advancement of technology has resulted in a more user-friendly virtual learning environment, this study aimed to investigate the implementation of Online PBL in teaching 4Cs. A total of 33 fifth-semester students, 22 females & 11 males, of a public university in Central Java were involved in this study. Observation and Likert-scale questionnaires were employed in collecting the data.Â By calculating the overall score per item, the data were analyzed using descriptive statistics. The result of this study shows five stages of Online PBL implementation starting from selecting the topic and the purpose, outlining the project, rehearsing the product, presenting the product, and assessing the product. Online PBL helps students to master creativity and innovation skills, communication skills, critical thinking skills, and collaboration skills. Based on the positive responses from students, Online PBL becomes a suggested method for assisting students in acquiring the 4Cs.